Conservative Management of Common Bile Duct Stones Post-Sleeve Gastrectomy: A Case Report on the Role of Glucagon and Subsequent Laparoscopic Cholecystectomy - Dani Osman; Etienne El-Helou; Mohamed Imad Abdelrhim Hassan; Hassan Marwan Hassan Ahmed; Wadah Yasin Deba; Ahmed Magdy Saleh Mohamed; Feras Al Rawashdeh; Nasser Alrashidi (Dr. Sulaiman Al Habib Medical Journal)
Obesity is a significant global health concern, leading to the widespread adoption of bariatric procedures such as laparoscopic sleeve gastrectomy (LSG). However, the rapid weight loss following LSG can predispose patients to biliary complications, including common bile duct (CBD) stones. This report describes the case of a 20-year-old female who developed CBD stones and pancreatitis two weeks after undergoing LSG. She presented with severe epigastric pain, nausea, vomiting, and constipation. Imaging revealed biliary dilatation with two small CBD stones but no gallbladder pathology. The initial plan included endoscopic retrograde cholangiopancreatography (ERCP), followed by elective laparoscopic cholecystectomy. During her hospital stay, the patient received multiple doses of glucagon hydrochloride, a pharmacological agent that relaxes the sphincter of Oddi. Remarkably, follow-up magnetic resonance cholangiopancreatography showed spontaneous resolution of the CBD stones without the need for ERCP. Subsequently, the patient underwent a successful laparoscopic cholecystectomy and was discharged in good condition. This case underscores the potential of conservative management using glucagon for select patients with small CBD stones, especially in the postbariatric population, where minimizing the risks of invasive procedures is crucial. The success of this approach highlights the importance of individualized care and multidisciplinary collaboration in managing postLSG biliary complications. Further research is warranted to establish the role of glucagon as a noninvasive treatment option for CBD stones.